2015
DOI: 10.1080/17448689.2015.1009696
|View full text |Cite
|
Sign up to set email alerts
|

Europeanize for Welfare? EU Engagement among Swedish Civil Society Organizations

Abstract: This article explores how and why Swedish-based civil society organizations (CSOs) in the welfare area engage with the European Union (EU). Europeanization is understood as a twosided process in which the EU influences national actors while national actors are engaged in usage of the EU. The data collection was conducted through a systematic study of the websites of organizations that participated in the Swedish Compact, and through subsequent e-mail interviews with representatives from 56 of those same organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…This trade-off seems to be absent when it comes to the national level where embeddedness instead incentivizes Europeanization. This is consistent with a recent study about the Europeanization of organizations that were engaged in political consultations at the national level (Hedling & Meeuwisse, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This trade-off seems to be absent when it comes to the national level where embeddedness instead incentivizes Europeanization. This is consistent with a recent study about the Europeanization of organizations that were engaged in political consultations at the national level (Hedling & Meeuwisse, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…A more recent unpublished qualitative study conducted among Swedish CSOs that participated in a civil dialogue process at the national level in the social welfare area showed that many organizations had indeed undergone a process of Europeanization. The most common activities were membership and activities in CSO networks at the European level, participation in EU-funded projects, lobbying activities at the EU level, and making use of specific key persons as facilitators in contact with EU institutions (Hedling & Meeuwisse, 2015).…”
Section: Europeanization Of Swedish Csosmentioning
confidence: 99%
See 3 more Smart Citations